TGF-β1 Gene -509C/T Polymorphism and Coronary Artery Disease: An Updated Meta-Analysis Involving 11,701 Subjects - Li, Yan-yan; Zhou, Yan-hong; Gong, Ge; Geng, Hong-yu; Yang, Xin-xing (Frontiers in Physiology, 2017)
Background: The 509C/T polymorphism of the transforming growth factor-β1 (TGF-β1) gene may be associated with an increased risk of coronary artery disease (CAD). Individuals studies, however, fail to present a consistent result. Objective and methods: To investigate the relationship between TGF-β1 gene -509C/T polymorphism and CAD, we conducted a meta-analysis of 11,701 participants from 8 individual studies. The pooled odds ratios (ORs) and their corresponding 95% confidence intervals were evaluated by either a random or fixed effect model depending on the heterogeneity of the data set. Results: Our analysis detected a significant association between the TGF-β1 gene -509C/T polymorphism and CAD under allelic (OR: 1.130, 95% CI: 1.060–1.200, P=0.0001), recessive (OR: 1.390, 95% CI: 1.100–1.750, P=0.006), dominant (OR: 0.857, 95% CI: 0.785–0.935, P=2.507×10-4), homozygous (OR: 1.258, 95% CI: 1.098–1.442, P=0.001), heterozygous (OR: 1.147, 95% CI: 1.046–1.257, P=0.003), and additive genetic models (OR: 1.131, 95% CI: 1.063–1.204, P=5.442×10-5). The subgroup analysis of the Chinese population found a significant association under all the genetic models, except the heterozygous genetic model (P>0.05). In the Caucasian subgroup, we once again found a significant association under all genetic models, save one. Here, our results under the recessive genetic model were not significant. (P>0.05). Conclusions: TGF-β1 gene -509C/T polymorphism is significantly associated with an increased risk of CAD. In other words, individuals with the T allele of TGF-β1 gene -509C/T polymorphism may be genetically predisposed to developing CAD.